2018
DOI: 10.1200/jgo.17.00063
|View full text |Cite
|
Sign up to set email alerts
|

Availability of WHO Essential Medicines for Cancer Treatment in Botswana

Abstract: PurposeStock outs of cancer drugs are potentially fatal but have not been systematically studied in low- and middle-income countries. The aim of this study was to determine the availability and alignment of the Botswana National Essential Medicines List (NEML) for cancer drugs with the WHO’s Essential Medicines List (EML).MethodsThe availability and cost of cancer drugs were analyzed using data from a weekly stock catalog sent by Botswana’s Central Medical Store to all pharmacy departments in government hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 15 publications
0
51
0
Order By: Relevance
“…It would also allow other cancer medicines to be considered for inclusion on the World Health Organization Model Lists of Essential Medicines. Table describes some methods to help reduce cancer medicine prices …”
Section: Approaches To Decreasing Cancer Medicine Costsmentioning
confidence: 99%
See 3 more Smart Citations
“…It would also allow other cancer medicines to be considered for inclusion on the World Health Organization Model Lists of Essential Medicines. Table describes some methods to help reduce cancer medicine prices …”
Section: Approaches To Decreasing Cancer Medicine Costsmentioning
confidence: 99%
“…To optimize outcomes, evidence‐based, economically wise practice must be emphasized throughout the cancer care process, from diagnosis and prescribing to dispensing and administration. Systems should be in place to identify and address problematic cancer medicine use (eg, tracking local and national cancer medicine use to forecast future use, purchase, and budgets and to prevent stock shortages that cause missed treatment) …”
Section: Concurrent Support To Optimize the Use Of Cancer Medicinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate infrastructure and health workers are also needed to manage acute complications of treatment administration. A recent study on the availability of WHO essential medicines reported frequent unavailability of cisplatin in some countries in Africa [32]. In other high incidence countries where drugs are available and subsidised for patients below the poverty line, approvals may be needed for weekly cycles [33], leading to delays in the implementation of an effective concurrent chemoradiation schedule.…”
Section: Access and Delivery Of Concurrent Chemotherapy For Cervical mentioning
confidence: 99%